The Coronavirus PEDV Evades Type III Interferon Response Through the miR-30c-5p/SOCS1 Axis - Wang, Changlin; Shan, Lingling; Qu, Shuxin; Xue, Mei; Wang, Keliang; Fu, Fang; Wang, Lu; Wang, Ziqi; Feng, Li; Xu, Wanhai; Liu, Pinghuang (Frontiers in Microbiology, 2020)
Porcine epidemic diarrhea virus (PEDV) is an economically important pathogen that has evolved several mechanisms to evade type I IFN responses. Type III interferon (IFN-λ), an innate cytokine that primarily targets the mucosal epithelia, is critical in fighting mucosal infection in the host, and has been reported to potently inhibit PEDV infection in vitro. However, how PEDV escapes IFN-λ antiviral response remains unclear. In this study, we found that PEDV infection induced significant IFN-λ expression in type I IFN-defective Vero E6 cells, but virus-induced endogenous IFN-λ did not reduce PEDV titers. Mechanistically, we demonstrated that PEDV escaped IFN-λ responses by substantially upregulating the suppressor of cytokine signaling protein 1 (SOCS1) expression, which impaired the induction of IFN-stimulated genes (ISGs) and dampened the IFN-λ antiviral response and facilitated PEDV replication in Vero E6 cells. We further showed that PEDV infection increased SOCS1 expression by decreasing host miR-30c-5p expression. MiR-30c-5p suppressed SOCS1 expression through targeting the 3' untranslated region (UTR) of SOCS1. and The inhibition of IFN-λ elicited ISGs expression by SOCS1 was specifically rescued by overexpression of miR-30c-5p. Collectively, our findings identify a new strategy by PEDV to escape IFN-λ-mediated antiviral immune responses by engaging SOCS1/miR-30c axis, thus improving our understanding of its pathogenesis.